Communism, Political Power and Personal Freedom in Marx - del Aguila Marchena, Levy. author. aut Link
XX, 282 p. 1 illus.
Keywords: This book investigates communism in Marx’s writings, incorporating a consideration of communist politicity. The author outlines the arguments by which it is possible to sustain—from Marx—the idea that human emancipation against capital also means the elimination of the State, the public, and the political dimension of praxis. He also posits that the concrete tasks of the “management of the common” in a communist society require political mediations that allow us to confront the difference inherent to the personality of freely associated producers, as well as the ontological finitude from which no technical power can evade. Finally, assuming Marx as a starting point whose work remains an inescapable source for “thinking communism,” the book proposes a research agenda from Marx and beyond to continue in this imperative task. Levy del Aguila Marchena is Senior Professor and Chair of the Department of Management Sciences at the Pontificia Universidad Católica del Perú. He has published extensively on Marx, political philosophy, and applied ethics.